Analysis of Improving Mathematical Analogy Ability in Snow Cube Throwing Based on Exploration Learning - Sari, Nenden Mutiara; Munawar, Hanhan Subhan (Universitas Sarjanawiyata Tamansiswa, 2021)
The snow cube throwing learning was developed to find patterns, make hypotheses, and draw conclusions based on their findings in problem-solving. Students are given five types of teaching materials with similar problems to improve students' mathematical analogy skills. This study aims to analyze the differences in the improvement of mathematical analogy abilities that received snow cube throwing based on exploration (SCTBE), exploratory and expository learning reviewed as a whole, and by school category. This study is a quasi-experimental study with a non-equivalent pretest and posttest control-group design. The research subjects were students of class VIII from three schools in Cimahi City. Overall, the results showed that students who received SCTBE and expository learning improved mathematical analogy abilities and were better than students who received exploratory learning. Reviewed by school category, SCTBE learning is more suitable for middle category schools with active and independent characteristics.